2011
DOI: 10.1111/j.1469-185x.2011.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding selection for long necks in different taxa

Abstract: There has been recent discussion about the evolutionary pressures underlying the long necks of extant giraffes and extinct sauropod dinosaurs. Here we summarise these debates and place them in a wider taxonomic context. We consider the evolution of long necks across a wide range of (both living and extinct) taxa and ask whether there has been a common selective factor or whether each case has a separate explanation. We conclude that in most cases long necks can be explained in terms of foraging requirements, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 64 publications
1
57
0
Order By: Relevance
“…raising the neck and supplying it and the head with blood). Model calculations specifically addressing low browsing in sauropods [61], [128] also confirm the hypothesis that the long neck greatly reduced the need for the animal to change its location during feeding. This would have resulted in energy savings of 80% in a Brachiosaurus bearing a nine-meter neck compared to a minimally-necked one [61].…”
Section: Test Of the Sauropod Gigantism Ecm By New Evidencementioning
confidence: 77%
See 4 more Smart Citations
“…raising the neck and supplying it and the head with blood). Model calculations specifically addressing low browsing in sauropods [61], [128] also confirm the hypothesis that the long neck greatly reduced the need for the animal to change its location during feeding. This would have resulted in energy savings of 80% in a Brachiosaurus bearing a nine-meter neck compared to a minimally-necked one [61].…”
Section: Test Of the Sauropod Gigantism Ecm By New Evidencementioning
confidence: 77%
“…Model calculations specifically addressing low browsing in sauropods [61], [128] also confirm the hypothesis that the long neck greatly reduced the need for the animal to change its location during feeding. This would have resulted in energy savings of 80% in a Brachiosaurus bearing a nine-meter neck compared to a minimally-necked one [61]. Both studies [61], [128] independently concluded that the energetic advantage of neck length levels off eventually with increasing neck length.…”
Section: Test Of the Sauropod Gigantism Ecm By New Evidencementioning
confidence: 77%
See 3 more Smart Citations